Fine Particulate Matter Related to Multiple Sclerosis Relapse in Young Patients - Januel, Edouard; Dessimond, Boris; Colette, Augustin; Annesi-Maesano, Isabella; Stankoff, Bruno (Frontiers in Neurology, 2021)
Objective: Particulate matter (PM) of aerodynamic diameter smaller than 10 µm (PM10) has been associated with multiple sclerosis (MS) relapse. However, the impact of smaller PM with a greater ability to penetrate human organism has never been assessed. We evaluated the impact of PM smaller than 2.5 µm (PM2.5) on the risk of MS relapse. Material and methods: In a case-crossover study, we included 2109 consecutive hospitalizations likely due to MS relapse in day hospital in 5 MS centers in the Paris area from January 2009 to December 2013. For each hospitalization, the natural logarithm of the average weekly PM2.5 concentrations (µg/m3) at the patient’s residence address during each of the six weeks (week[0] to week[-5]) preceding admission was compared with the concentration during the previous week, using a conditional logistic regression adjusted on temperature, flu like syndrome rate, pollen count, and holiday period. Results: PM2.5 average concentration during week[-3] was significantly associated with the risk of hospitalization for MS relapse (OR=1.21 [CI 1.01;1.46]). The association was stronger in patients younger than 30 years (OR=1.77 [CI 1.10;2.83]). Conclusion: Our study demonstrates an association between exposure to PM2.5 and MS relapse, particularly in young people.